Temporal sustainability of guideline based door-to-needle times for intravenous thrombolysis for acute ischemic stroke. (April 2020) - Raina, Abhinav; Trivedi, Madhukar; Kate, Mahesh; Kumar, Laisa; Erat Sreedharan, Sapna; Sylaja, PN
Highlights: Better door-to-needle times are possible with hospital systems training. Door-to-needle times need revision with less than 60 min. Hospital system do not develop campaign fatigue. Abstract: Background: Door to needle (DTN) time provides valuable insight into stroke care workflow and is a performance indicator of an acute stroke unit. The aim of the current study was to ascertain whether a door to needle time of less than 60 min can be achieved for intravenous thrombolysis (IVT) in acute ischemic stroke (AIS) and maintained long term in a comprehensive stroke unit. Methods: Patients with AIS treated with IVT in the stroke unit formed the study group. Demographic and clinical characteristics including door to imaging (DTI) time, DTN time, and 3 month functional outcome were abstracted. Pairwise comparison was done of yearly median DTI and DTN times with Bonferroni correction. Results: Over a period of 6 years a total of 196 patients with mean age of 61.5 ± 13.1 years and median (IQR) NIHSS 11 (8–16) underwent IVT. The median DTI time and DTN time over the study period was 15 (12–21) minutes and 40 (30–50) minutes respectively. A total of 90.1%, 69.4% and 29.1% patients received IVT within 60 min, 45 min and 30 min respectively. On pairwise comparison of the median yearly DTN Year 2016 and 2017 were lower compared to most of the earlier years (p < 0.0001). Good functional outcome (mRS ≤ 2) was noted in 68.7% patients at 3 months follow-up. Conclusion: It is possible to sustainably reduce DTN time for IVT in AIS to well below the current 60 min benchmark with hospital system training and teamwork.